Similarities and differences between impulse buying and variety seeking. - Chew, Yuet Ling. (2008)
This paper is a research on the similarities and differences between impulse buying and variety seeking. Factors explored in this paper are self-monitoring, optimal stimulation level, private/public situations, impulsiveness and product categories. The research method used is a mall-intercept survey.